Use of Ability Grouping in Mathematics Teaching - Roka, Jasbir (Academic Journal of Mathematics Education, 2022)
Grouping by ability refers to procedures of classes formation based on students' academic achievement. The main purpose of the study is to analyze relation between ability grouping and mathematics achievement at secondary level. As a qualitative study, the information has been collected through research articles, books, and reliable documents. It is found that their ability grouping is more beneficial to high-level students rather than low level-students. Also it is found that the majority of mathematics teachers and gifted/talented student have positive attitudes towards grouping by students' abilities. It is recommended that mixed-ability grouping should be used in the context of mathematics classrooms in Nepal.